Association between high blood pressure and fitness and fatness in adolescents (2020)
ABSTRACT: Introduction: Excess adiposity is considered the most important risk factor for high blood pressure (HBP) in children and adolescents.Objectives: To explore the association between HBP and overweight (OW) and abdominal obe-sity (AO), mediated by cardiorespiratory fitness (CRF). To analyze the combined effect of excess adiposity and CRF on HBP among a sample of school-aged children from Montería, Colombia.Materials and methods: Cross-sectional study conducted in a sample of 546 adolescents aged between 11 and 18 years from 14 randomly selected schools in Montería. Blood pres-sure, anthropometric, and fitness measures were evaluated by trained personnel using standardized protocols and instrumentation. The association of HBP with fitness and fatness was analyzed using logistic regression models.Results: HBP was associated with OW, AO and low CRF. The inclusion of CRF in this model did not attenuate the association between HBP and OW and between HPB and AO. Adoles-cents with higher adiposity and low CRF were more likely to have HBP compared with those with lower adiposity and high CRF. Moreover, it was found that excess adiposity and low CRF had an additive effect on the risk for HBP among the sample.Conclusion: HBP is a prevalent condition in children and adolescents from Montería, Co-lombia. HBP is significantly associated with OW, AO, and low CRF; therefore, it is necessary to implement initiatives to promote healthy habits aimed at this population in order to re-duce the incidence rate of HBP in Colombian adolescents.